Mentalizing Skills Deficits in Schizophrenia as a Clue for Drug Choice: Clozapine Versus Other Antipsychotics on Keeping Outpatients Stable - Duñó, Rosó; Langohr, Klaus; Palao, Diego; Tobeña, Adolf (IntechOpen, 2012)
None